How Interpersonal Communication And Physical Work Environment Affect The Employee’ Performance At Quality Control Division Of PT. Bangun Beton - Suhartini Suhartini; Ratu Dea Mada Badriyah; Ade Nahdiatul Hasanah (Fakultas Bisnis, 2020)
This research aims to determine the effect of interpersonal communication and physical work environment on the employees’ performances of PT Bangun Beton Quality Control division -. This research was conducted with quantitative methods. The research population was 54 people using saturated samples. The study was conducted at PT Bangun Beton Quality Control Division on November 28 to May 29, 2019. Data was collected by questionnaire, and analyzed by IBM SPSS Statistic v.24.The results showed there was a significant negative effect between interpersonal communication on employee performance based on a partial test (t test) using a significance level of 0.05%, then there was a significant positive effect between the physical work environment on employee performance based on a partial test (t test) using significant level of 0.05%. The F test shows that interpersonal communication and physical work environment together have an influence on employee performance